Anthropometric profiles in table tennis players: Analysis of sex, age, and ranking - Pradas, F.; de la Torre, A.; Carrasco, L.; Muñoz, D.; Courel-Ibanez, J.; González-Jurado, J .A. (Applied Sciences, 2021)
Table tennis has recently evolved towards a more spectacular sport increasing match-play demands and the intensity and speed of actions by regulations and equipment modification. Since these changes can alter the body composition and performance, this study aimed to analyze the differences in anthropometric attributes of 495 table tennis players (288 men, 207 women) according to sex, age, and ranking. Players were classified according to sex, age categories (Senior, Under-18, Under-15, Under 13, and Under 11), and ranking position. Anthropometry measurements included eight skinfolds` thicknesses (biceps brachii, triceps, subscapular, iliac crest, supraspinal, abdominal, thigh, and medial calf), four girths (biceps brachii relaxed and contracted, thigh, and calf), and three breadths (biepicondylar femur, biepicondylar humerus, and bistiloyd wrist) to determine fat mass, lean mass, bone, cross sectional area (CSA) for arm, leg, and thigh, and somatotype. Results revealed that table tennis players presented differences in body mass composition, anthropometry, and somatotype according to sex and age category and ranking. It seems confirmed that regular table tennis practice during the childhood is associated with a healthy body composition status, that appears to be maintained across older ages if keeping the practice. Senior table tennis players showed a fat mass <20% and lean mass ~45% in men and ~37% in women. A new contribution is that higher lean mass in the upper limbs was associated with higher ranking position (i.e., better performance), endomorphic somatotypes were negative related to performance, and ectomorphic profiles seems more effective, which suggest the potential influence of morphologic changes in table tennis competition performance.